Pengaruh Media Sosial Instagram Terhadap Budaya Hedonisme Generasi Millenial di Madiun - Fahmi Andayani (Persepsi: Communication Journal, 2022)
AbstractAdvances in technology and information at this time bring changes from various aspects of people's lives. The emergence of social media as one of the evidences of technological advances makes people's behavior patterns change both from cultural aspects, ethics to norms. Ease of accessing social media is one of the causes The emergence of a hedonistic lifestyle in the millennial generation. For some people, lifestyle is important as a form of self-expression. Millennials who have a hedonistic lifestyle tend to comply with desires rather than needs. social media among millennials. By using a qualitative descriptive method, this research is expected to explain the hedonistic lifestyle that appears in the millennial generation and the importance of being wise in using social media. The data analysis technique in this study uses redux. i data, presentation of data and drawing conclusions. The results of the study show that the influence of social media Instagram on the hedonic lifestyle of the millennial generation is at a moderate level, which means that this generation is occasionally hedonistic when it is in a state of being able to both from environmental, family and cultural factors.Keywords: Social media, culture, hedonism, lifestyle